2001
DOI: 10.1074/jbc.m006353200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Autonomous Apoptosis Defects in Acid Sphingomyelinase Knockout Fibroblasts

Abstract: A body of evidence suggests that stress-induced sphingomyelin hydrolysis to the second messenger ceramide initiates apoptosis in some cells. Although studies using lymphoblasts from Niemann-Pick disease patients or acid sphingomyelinase (ASMase)-deficient mice have provided genetic support for this hypothesis, these models have not been universally accepted as definitive. Here, we show that mouse embryonic fibroblasts (MEFs) prepared from asmase mice manifest cell autonomous defects in apoptosis in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 52 publications
2
64
0
1
Order By: Relevance
“…Most importantly, the sensitivity to stress could be restored in the asmaseÀ/À MEFs by administration of natural ceramide. 44 We observed that C2 ceramide, a cell-permeable analogue of ceramide, activates cell death in a number of human cell lines, as previously described in publications from many different laboratories. Quite paradoxically, we have found that C2 ceramide activates, at the same time, an NF-kBdependent survival pathway through calpain, in accordance with a previous report.…”
Section: Discussionsupporting
confidence: 72%
“…Most importantly, the sensitivity to stress could be restored in the asmaseÀ/À MEFs by administration of natural ceramide. 44 We observed that C2 ceramide, a cell-permeable analogue of ceramide, activates cell death in a number of human cell lines, as previously described in publications from many different laboratories. Quite paradoxically, we have found that C2 ceramide activates, at the same time, an NF-kBdependent survival pathway through calpain, in accordance with a previous report.…”
Section: Discussionsupporting
confidence: 72%
“…171,[302][303][304] As cells deficient for acidic SMase are still TNF sensitive, 305 TNFinduced ceramide production seems to have no general, obligatory role in TNF-induced cell death. Nevertheless, the demonstration of reduced TNFsensitivity of aSMaseÀ/À mouse embryonic fibroblasts 306 and several other studies point to aSMase and ceramide production as celltype specific modulatory factors of TNF-induced cell death. 307 TNF-R1-induced activation of aSMase occurs by a FADD-dependent, but caspase-8 independent pathway.…”
Section: Molecular Mechanisms Of Tnf-induced Cell Deathmentioning
confidence: 98%
“…The fluorogenic substrate Ac-DEVD-AFC (BD Biosciences, San Diego, USA) was used to measure caspase-3 activity according to Lozano et al [19]. Cell extracts were prepared as described by Wellington et al [20].…”
Section: Caspase-3 Activity Assaymentioning
confidence: 99%